Power, Profit and Inflation: A Study of Inflation and Influence in Pakistan - Syed Ozair Ali (The Bichler and Nitzan Archives, 2011)
An economist's take on differential accumulation and inflation in Pakistan. Our analysis seeks to look at inflation as a political economic phenomenon, based on a framework devised by Jonathan Nitzan and christened differential accumulation. The theory of differential accumulation rejects the conventional definitions of capital and draws upon Veblenian economics to integrate the definitions of power and capital by describing the ownership of capital as differential power claims over social processes. In order to maximize capital accumulation, businessmen allocate resources, in response to the socio-political environment, to beat a certain benchmark rate of return in their pursuit of maximizing capital accumulation. We find evidence for the existence of this phenomenon in Pakistan by assuming that a certain group of businessmen seeks to maximize power by maximizing relative profit, which in turn affects overall inflation. However, we have not established proof through a scientifically rigorous process due to incomplete datasets. We believe that these findings merit further investigation and propose that the maximization of relative profit as opposed to absolute profit, may, in fact, be a behavioral phenomenon. Such a finding will merely be the doppelganger of the maximization of relative utility, as opposed to absolute utility, in consumer decision-making models.
Keywords: 330; differential; accumulation; dominant; capital; inflation; Pakistan